Good Governance: Performance Values and Procedural Values in Conflict. (November 2015) - de Graaf, Gjalt; Paanakker, Hester
Good governance codes usually end with a list of public values no one could oppose. A recurrent issue is that not all of these values—however desirable they are—can be achieved at the same time. With its focus on performance and procedural values of governance, this article zooms in on the conflict between two different types of values, signifying and exemplifying how output and outcome on one hand and the process of governance on the other may coincide or collide. The main research question is, "What is the nature of value conflict in public governance and what specific conflicts between performance and procedural values do public actors perceive?" A literature review and two case studies involving aldermen and the most senior public administrators in public governance set out to answer these questions. The most frequently perceived conflict is between lawfulness and transparency in procedure, on one hand, and the attainment of effectiveness and efficiency as performance values on the other.